Foliar nutrient concentration in teak plantations at the Panama Canal watershed - Murillo, Rafael (2014)
Foliar concentration of macro- and micronutrients in teak plantations at the Panama Canal Watershed was measured on sites classed as high, medium, and low in growth (volume.ha -1 ). For the same purpose, plantations where grouped by age as young (3-4 years), medium (5-6 years) and late (7-8 years). Foliar macro-nutrients concentration followed the order N (1,9%), Ca (1.1%), K (0.7%), S (0.2%) and P (0.1%), while micro-nutrients concentrations decreased in the order Mn (50), Fe (43), Al (36), B (29), Zn (28), Cu (8), and Mo (0.4) mg.kg -1 . The K, P and Fe concentrations were clearly identified as low, while N, Ca, Mg and Mn values can be considered as marginal to slightly low. The Ca, Mg, N, K, Mn, Zn, Fe and Al concentrations varied statistically with plantation age in different ways; foliar concentrations of Ca, Mg, Mn, Fe and Al tend to increase with age, while those of N, K and Zn tend to diminish with age. Concentrations of Ca and Mn in the leaves of trees of sites with high and low growth differed statistically (p<0.01), with Ca values of 1.18% and 0.99%, in the high and low growth categories, respectively, and with Mn values of 41 and 65 mg.kg -1 in sites of high and low growth rates, respectively.